2002
DOI: 10.1038/sj.sc.3101348
|View full text |Cite
|
Sign up to set email alerts
|

Complications of intermittent catheterization: their prevention and treatment

Abstract: Study design: Literature review to evaluate the complications seen in patients on intermittent catheterization (IC) and intermittent self-catheterization (ISC). Objectives: To ®nd the prevalence of most complications seen in patients on IC. To study the prevention and the treatment of these complications. Setting: An international literature review. Methods: Most relevant articles on the subject are reviewed. Conclusion: Urinary tract infection is the most frequent complication in patients performing IC. Cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
146
2
21

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 59 publications
8
146
2
21
Order By: Relevance
“…There is strong argument regarding the safety and efficacy of IC for treatment of neurogenic bladder dysfunction in patients with spinal cord lesions. 23 IC is considered preferable to other forms of bladder emptying in neuropathic patients as it has less complications and associated with a better outcome. 23 We investigated previously changes in BP, pulse rate and classic symptoms of AD before, during and after a bowel program involving manual removal of stool in lateral recumbency in patients with cervical SCI and AIS A or B grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong argument regarding the safety and efficacy of IC for treatment of neurogenic bladder dysfunction in patients with spinal cord lesions. 23 IC is considered preferable to other forms of bladder emptying in neuropathic patients as it has less complications and associated with a better outcome. 23 We investigated previously changes in BP, pulse rate and classic symptoms of AD before, during and after a bowel program involving manual removal of stool in lateral recumbency in patients with cervical SCI and AIS A or B grade.…”
Section: Discussionmentioning
confidence: 99%
“…23 IC is considered preferable to other forms of bladder emptying in neuropathic patients as it has less complications and associated with a better outcome. 23 We investigated previously changes in BP, pulse rate and classic symptoms of AD before, during and after a bowel program involving manual removal of stool in lateral recumbency in patients with cervical SCI and AIS A or B grade. 11 The insertion of rectal medication induced a significant increase in systolic BP, which persisted during additional digital rectal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it demands specially trained medical resources as well as enough time to give the patients the relevant information and to train them to acquire a proper CIC technique. Wyndaele 19 suggested that the most important measures were a good education of all factors involved in intermittent catheterization, good patient compliance, the use of proper materials, and the application of a good catheterization technique.…”
Section: Discussionmentioning
confidence: 99%
“…Doing so, it is evident that intermittent catheterization is superior to indwelling catheters of any kind. [2][3][4] In this case, no misunderstanding about the status of indwelling catheters in the treatment of patients with neurogenic bladder dysfunction due to spinal cord injury would have been possible.…”
mentioning
confidence: 92%